Changes in hospital efficiency after privatization - Oliver Tiemann; Jonas Schreyögg (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2011)
We investigated the effects of privatization on hospital efficiency in Germany. To do so, we obtained bootstrapped DEA efficiency scores in the first stage of our analysis and subsequently employed a difference-in-difference matching approach within a panel regression framework. Our findings show that conversions from public to private for-profit status were associated with an increase in efficiency of between 3.2 and 5.4%. We defined four alternative post-privatization periods and found that the increase in efficiency after a conversion to private for-profit status appeared to be permanent. We also observed an increase in efficiency one year after hospitals were converted to private non-profit status, but our estimations suggest that this effect was transitory. Our findings also show that the efficiency gains after a conversion to private for-profit status were achieved through substantial decreases in staffing ratios in all analyzed staff categories with the exception of physicians. It was also striking that the efficiency gains of hospitals converted to for-profit status were significantly lower in the DRG era than in the pre-DRG era. Altogether, our results suggest that converting hospitals to private for-profit status may be an effective way to ensure the scarce resources in the hospital sector are used more efficiently.
Keywords: I11; I12; L20; L33; M11; 330; Privatization; Performance measurement; Data envelopment analysis; Propensity score matching; Germany; Krankenhaus; Privatisierung; Wirtschaftliche Effizienz; Data-Envelopment-Analyse